ASYMMETRY OF SOMATOSENSORY CORTICAL PLASTICITY IN PATIENT WITH BILATERAL CARPAL TUNNEL SYNDROME (International Journal of Physiotherapy, 2017)
Background: Following peripheral nerve lesion, the adult somatosensory system showedcortical reorganizational abilities.Previous studies identified the digits' somatotopy map changes and somatosensory cortical plasticity in response to the Carpal Tunnel Syndrome (CTS) that affected the dominant hand only. Objective: Answering the remained question is that what the extent of the cortical plasticity would be in left and right somatosensory cortices in response to CTS affecting the right and left hands simultaneously.Methods: Cortical representations activated by tactile stimulation of median nerve (index) and ulnar nerve (little) of both dominant and non-dominant hands were evaluated by Magnetoencephalography (MEG) systemfor healthy participants and patient with bilateral moderate CTS. index – little fingers'somatotopy map and inter-digit cortical distance was then mapped and calculated for each participant on the real MRI data and the 3D brain surface image.Results: in healthy participants, index – little inter-digit somatosensory cortical distance of right hand (dominant) was significantly larger than the index – little inter-digitsomatosensory cortical distance of left hand (11.2±2.1mm vs.7.0±2.9mm, P = 0.006). However, in patient with bilateral CTS, the index – little inter-digit somatosensory cortical distance of righthand (dominant) was significantly smaller than the index – little inter-digit somatosensory cortical distance of left hand (5.8mm vs. 7.4mm).Conclusion: our data could be interpreted as the hand use – dependency served more median nerve – cortical territory from the ulnar nerve invasion in the right somatotopy map (left hand) than the left somatotopy map of the right hand.